Three hundred:: active and collaborative learning as an alternative to the problem of test anxiety - Fragelli, Ricardo Ramos (Revista Gestão & Saúde, 2015)
There are several factors that influence the low index graduates in engineering courses such as the lack of sufficient previous concepts for meaningful learning, the gap between what is taught and the labor market and the insistence on the traditional model of teaching and learning that in most cases, it is shown inefficient. However, a very important and underexplored aspect is related to the strategy of assessment used learning,especially concerning the stress and anxiety it causes in some students. In this context, this paper aims to present the continuation of a project entitled "Humanized Test" that studied the constructs of nervousness and anxiety of first-year students in tests. In the first stage, it observed that 67% of research participants had a level of anxiety that can cause low performance in assessments and in 44% of texts there was the terms such as "insecurity", "nervousness" and "anxiety". In the second stage, we attempted to use one methodologie based on active and collaborative learning to resolve this problem and resulted in an improvement in the pass rate and in controlling anxiety.